Analisis Kesulitan dalam Menyelesaikan Soal Luas Bangun Datar Gabungan Siswa Kelas IV SD - Azka Salmaa Salsabilah; Nabila Putri Nur Afifah; Rachel Fadila Putri Herdiansyah; Komariah Komariah (Departement of Mathematics Education, 2023)
Geometry is a branch of mathematics and is one of the subject matter in mathematics in elementary school. Students often make mistakes in solving geometry problems. The difficulty experienced by these students in solving the problem is due to not being able to understand the meaning of the problem and confusion when determining the formula to be used. The purpose of this study was to analyze the difficulties of grade IV students of SDIT Al-Mumtaz in solving the problem of the area of combined flat shapes. This research uses descriptive qualitative research in the form of essay tests (questions) totaling 2 questions during the learning process and 2 questions during the learning evaluation. The research subjects were fourth grade students totaling 17 students. The data analysis technique used in this research is descriptive. The results showed that there were difficulties faced by students in solving problems of combined flat shapes, these difficulties included (1) difficulty determining data (type I difficulty), (2) difficulty remembering formulas (type II difficulty), and (3) calculation difficulties (type III difficulty).